Evaluation of the Effects of the Belt and Road Initiative on the Unified Economic and Environmental Efficiency of Transportation Infrastructure in China Based on Range-Adjusted Measure Model and Difference in Difference Model - Yijiao Wang (Complexity)
The Belt and Road Initiative has brought new opportunities for countries along the routes to develop their transportation infrastructure. Through large-scale transportation infrastructure construction, these countries enhanced the Belt and Road cooperation with each other, which further facilitates the rapid development of their own economy, but whether this can promote the sustainable development of their own environment, relevant research is still lacking. In this paper, China is taken as the study subject to evaluate the comprehensive effects that the Belt and Road Initiative exerts on the economy and environment through improving transportation infrastructure. In the study, RAM indicators were first established to measure the unified economic and environmental efficiency of transportation infrastructure, a DID model was then built to study the effects of the Initiative on the unified efficiency, and mediation models were finally created to discuss the ways in which the Belt and Road Initiative can improve the unified economic and environmental efficiency of transportation infrastructure through transformation and upgrade of industrial structure. The study result shows that the Belt and Road Initiative can significantly promote the improvement of the unified economic and environmental efficiency of the national transportation infrastructure, but the result is regionally heterogeneous. The Initiative has positive effects in improving the unified efficiency in eastern region but has no effect in the central and western regions. Although the Initiative can significantly enhance the efficiency through transforming and upgrading the industrial structure, the industrial structure rationalization plays a primary positive role. This paper provides the empirical evidences to evaluate the implementation effects of the Initiative in the transportation infrastructure sector and verifies that countries along the routes can achieve sustainable development through large-scale transportation infrastructure construction under the Belt and Road Initiative.